Kadar Prostaglandin F2? pada Cairan Vesikula Seminalis dan Produk Sel Monolayer Vesikula Seminalis Sapi Bali (CONCENTRATIONS OF PROSTAGLANDIN F2? IN SEMINAL VESICLE FLUID AND PRODUCT OF SEMINAL VESICLE MONOLAYER CELLS OF BALI CATTLE) - Oka Pemayun, Tjok Gde (Jurnal Veteriner; Vol 8 No 4 (2007), 2007)
In this study, the concentration of prostaglandin F2 ? (PGF2?) in seminal vesicle fluid and seminal vesicle monolayer cell cultures of Bali cattle was determined. The seminal vesicle fluid was aspirated and the epithelial cells of the seminal vesicles were cultured in tissue culture medium (TCM) 199 growth medium containing 10% fetal calf serum (FCS) and 10% oestrus mares serum (EMS) with a density of 1.9 x 106 cells / ml medium. Following an incubation at 38.50 C in 5% CO2 atmosphere for 6 days and the level of PGF2 ? in the original seminal vesicle fluid and in the cell culture medium were determined by radioimmunoassay techniques (RIA). The results showed that the level of PGF2 ? in the non-extracted monolayer culture of seminal vesicle (1287,50 ± 3,39 pg/ml ) was significantly higher than that of detected in non-extracted seminal vesicle fluid (1,23 ± 0,79 pg/ml). In contrast, after extraction the level of PGF2 ? in seminal vesicle monolayer cell cultures (218,33 ± 2,87 pg/ml) significantly decreased as compared to seminal vesicle fluid (1750,83 ± 2,71 pg/ml). In conclusion the highest level of PGF2 ? was found in the extract of seminal vesicle fluid.
Keywords: Seminal Vesicle, PGF2 ?, Bali Cattle